Knowledge Management To Improve Local Government Services: Knowledge Management - Sadat, Anwar (International Journal of Science, Technology & Management, 2021)
This study aimed to improve the service of local governments in combining existing knowledge in an organization so that it can create, collect, maintain and manage employee knowledge and performance through the mastery of knowledge by all members. When knowledge sharing has been successfully applicated in ensuring the services survived in which each apparatus can synergy to achieve better performance to achieve common goals. employees in the Regional Government experience high mobility between agencies in the regions with various basic tasks and functions. Therefore, we need a high adaptability by an employee to be able to carry out tasks in a new place as quickly as possible. This condition results in an agency that is very important to manage its resources in order to support every employee (HR) possessed to carry out their duties properly even though the employee concerned has just entered his institution. This is where the importance of knowledge management or knowlegde management can be felt to keep the organization moving forward despite facing various situations that affect the performance of achieving organizational goals. This study uses a qualitative approach to the type of instrumental case study research. The location of the study was conducted at the Baubau City Regional Secretariat. Data collection techniques used, namely: in-depth interviews, document studies and observations. The results showed that Knowledge Management is an effort to improve the performance capabilities of local government apparatus services in managing their intellectual assets, in the form of existing knowledge and experience. The aim is to utilize these assets to achieve better service performance to accelerate the achievement of the objectives implemented in accordance with bureaucratic reform